Synthesis and evaluation of novel HDAC inhibitors : modulation of chromatin structure - Carreira, Sara Isabel Nunes (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2014